Le Parti des Travailleurs à l’épreuve du pouvoir. Le PT dans le District Fédéral au Brésil (1980-2000) - Daniella de Castro Rocha (Nuevo mundo - Mundos Nuevos, 2008)
The Workers Party (PT) has been frequently mentioned as a paradigmatic case, as an improbable model of entry into politics for actors socially illegitimate. The purpose empirically established by the PT in Federal District (FD), has made it possible to revisit this paradigm intriguing. Having restored the conditions for the party in the FD, with a socio-historical analysis and a study of social and politics properties of its members, this thesis focuses on the ambiguous relationship of the petistas with power. Put to the test by the experience of the government in the region, the PT-FD saw a non homogeneous movement of restructuring. Among the effects of the tangled process generated within its inner space, we observe a qualitative transformation of the partisan link. One of the challenges in this thesis has been the construction of an analysis trying to report on the space positions of the organization and its entrepreneurial characteristics, without forgetting its « social institution » dimension, that gives coherence to the activists. The attempt to link a structural approach of this political party –centered by a structuring network and the dispositions they generate– and a processual approach –emphasizing the context– has been an extra theoretical challenge.